PENERAPAN KURIKULUM MERDEKA DALAM PEMBELAJARAN MATEMATIKA SMK DIPONEGORO BANYUPUTIH - DIAN LUTFIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Based on the Pancasila student profile, the independent curriculum prioritizes student learning outcomes. This study aims to describe the management of learning mathematics in an autonomous curriculum, including (1) planning for learning mathematics and (2) implementing the planning. (3) Monitor and assess students' mathematics learning outcomes. There is qualitative research in this study. information was collected through observation, interviews, documentation, and literature analysis. Data reduction techniques, data visualization, and drawing conclusions were used to analyze the data. (1) Based on the educational unit operational curriculum (KOSP) that has been implemented, the research results are used to make a schedule for learning mathematics at SMK Diponegoro Banyuputih. Mathematics teaching plans are made according to the characteristics of the educational environment and can accommodate the demands of students. (2) The implementation of mathematics learning at Diponegoro Banyuputih Vocational School uses various learning strategies to overcome difficulties according to the abilities or capacities of students. In the curriculum for independent learning, students are given the freedom (independence) to express themselves according to their expertise. (3) Evaluation of teacher mathematics learning follows the principles of assessment for independent learning age, namely authentic evaluation based on evaluation for evaluation purposes, evaluation for evaluation purposes, and evaluation for evaluation. ABSTRAKBerdasarkan profil siswa Pancasila, kurikulum merdeka mengutamakan hasil belajar siswa. Penelitian ini bertujuan untuk mendeskripsikan pengelolaan pembelajaran matematika dalam kurikulum otonom, meliputi (1) perencanaan pembelajaran matematika dan (2) pelaksanaan perencanaan tersebut. (3) Memantau dan menilai hasil belajar matematika siswa. Ada penelitian kualitatif dalam penelitian ini. informasi dikumpulkan melalui observasi, wawancara, dokumentasi, dan analisis kepustakaan. Teknik reduksi data, visualisasi data, dan penarikan kesimpulan digunakan untuk menganalisis data. (1) Berdasarkan kurikulum operasional satuan pendidikan (KOSP) yang telah dilaksanakan, hasil penelitian digunakan untuk membuat jadwal pembelajaran matematika di SMK Diponegoro Banyuputih . Rencana pengajaran matematika dibuat sesuai dengan ciri-ciri lingkungan pendidikan dan dapat mengakomodasi tuntutan siswa. (2) Pelaksanaan pembelajaran matematika di SMK Diponegoro Banyuputih menggunakan berbagai strategi pembelajaran untuk mengatasi kesulitan sesuai dengan kemampuan atau kapasitas siswa. Dalam kurikulum untuk belajar mandiri, siswa diberikan kebebasan (kemandirian) untuk mengekspresikan diri sesuai dengan keahliannya. (3) Evaluasi pembelajaran matematika guru mengikuti prinsip penilaian untuk usia belajar mandiri, yaitu evaluasi autentik berdasarkan evaluasi untuk kepentingan evaluasi, evaluasi untuk kepentingan evaluasi, dan evaluasi untuk evaluasi.